A comparative in vitro analysis of various temporization materials with respect to pulp chamber temperature changes during polymerization - Sneha Bharadwaj; Gopal Krishna Choudhury; Abhilash Mohapatra; Sangram Panda; Upasana Dhar (Wolters Kluwer Medknow Publications, 2024)
Aim: (1) To compare the temperature rise in the pulp chamber with different resin materials used for making provisional fixed partial dentures in anterior and posterior region while using Polyvinylsiloxane impression materials as matrix. (2) To identify a superior provisionalization material based on the amount of heat dissipated suitable for anterior and posterior provisional fixed partial denture fabrication. Settings and Design: Temporary crowns and bridges are integral to Fixed Prosthodontics. It has been observed that conventional fixed prosthesis temporisation materials release heat due to the exothermic polymerisation reaction. When such a provisional material is directly let to set on a vital tooth, the heat transfer causes irreversible changes in the pulp tissue depending of the degree of change. Hence, this study observes amount of heat generation in various materials during temporisation procedure, by simulating similar conditions. Materials and Methods: Two Models were fabricated, one simulating missing lateral incisor (Model A) and another simulating missing first molar (Model B). Intact maxillary central incisors and canine for Model A and intact mandibular Second Premolar and Second Molar were selected to act as abutments. These abutment teeth were fitted with the tip of a K-type Thermocouple inside their pulp chambers and these were connected to a digital thermometer. Five temporisation materials were chosen for fabrication of temporary crowns through Direct technique. (1) polymethy methacrylate (Self Cure acrylic), (2) bisacryl composite (Protemp 4), (3) visible light cure urethane dimethacrylate (Revotec LC), (4) barium glass and fumed silica infused methacrylate (Dentsply Integrity) and (5)nano-hybrid composite (VOCO Structur 3). Ten observations were made for each provisional material on each model. During each observation, temperature rise was recorded at 30s interval from the time of application, through the peak and till a decrease in temperature is observed. Polyvinyl siloxane was used as matrix for all except light cure resin, where polypropylene sheet was used. Statistical Analysis Used: Anova test used for statistical. Results: ANOVA test revealed that there was a significant difference in the temperature changes associated with the provisional restorative materials used. Among the five, polymethy methacrylate (self cure resin) showed the maximum rise in temperature, followed by bisacryl composite (Protemp 4), visible light cure urethane dimethacrylate (Revotec LC), barium glass and fumed silica infused methacrylate (Dentsply Integrity) and nano-hybrid composite (VOCO Structur 3). There was no comparable difference between Model A and B but an overall reduction of temperature rise was observed in model B. Conclusion: VOCO Structur 3 showed the least temperature rise in the pulp chamber, and overall temperature rise was less for model B which can be attributed to the residual dentin thickness.